+0  
 
0
36
2
avatar

Hallo, dies ist meine Frage: (19x-17)-(3x-72)=-13+(13x+83) Aufgabenstellung: Löse die Gleichung duch Umformen.

 26.03.2020
 #1
avatar+11685 
+1

(19x-17)-(3x-72) = -13+(13x+83)    Klammern auflösen

    19x-17-3x+72 = -13+13x+83       Zusammenfassen

             16x +55 = 13x+70              | -13x

               3x +55 = 70                     |-55

                      3x = 15                     | :3

                       x = 5  

laugh

 
 26.03.2020
 #2
avatar
+1

Dankeschön <3

 
Gast 26.03.2020

21 Benutzer online

avatar
avatar